2017
DOI: 10.1038/cddis.2017.468
|View full text |Cite
|
Sign up to set email alerts
|

The histone code reader Spin1 controls skeletal muscle development

Abstract: While several studies correlated increased expression of the histone code reader Spin1 with tumor formation or growth, little is known about physiological functions of the protein. We generated Spin1M5 mice with ablation of Spin1 in myoblast precursors using the Myf5-Cre deleter strain. Most Spin1M5 mice die shortly after birth displaying severe sarcomere disorganization and necrosis. Surviving Spin1M5 mice are growth-retarded and exhibit the most prominent defects in soleus, tibialis anterior, and diaphragm m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 69 publications
0
9
0
1
Order By: Relevance
“… 40 SPIN1 has also been shown to function as a histone code reader to control skeletal muscle functional networks. 41 In this work, we found that the miR-409/SPIN1 axis could regulate cell migration and proliferation in NSCLC cells through the PI3K/AKT pathway. We also identified that the SPIN1 overexpression directly promoted NSCLC progression.…”
Section: Discussionmentioning
confidence: 77%
“… 40 SPIN1 has also been shown to function as a histone code reader to control skeletal muscle functional networks. 41 In this work, we found that the miR-409/SPIN1 axis could regulate cell migration and proliferation in NSCLC cells through the PI3K/AKT pathway. We also identified that the SPIN1 overexpression directly promoted NSCLC progression.…”
Section: Discussionmentioning
confidence: 77%
“…Aging is complex set of genetic [40,41], epigenetic [4246], immunological [4751], and metabolic [5258] rearrangements, involving several cellular signalling pathways [5963] able to regulate metabolism, ROS formation [6471] and DNA Damage Response (DDR) [7274] in all organs [7577]. Therefore, the identification of novel pathways involving p53-mediated responses [78,79] is of crucial interest.…”
Section: Discussionmentioning
confidence: 99%
“…Myf5-Cre line we employed has been previously used to examine satellite cells in limb and extraocular muscles, to ablate embryonic myogenic cells, and to conditionally ablate genes in skeletal muscle (Comai et al, 2014;Gensch et al, 2008;Greschik et al, 2017;Kuang et al, 2007;Stuelsatz et al, 2014). We note that the Myf5-Cre allele may not be effecting a full deletion of Pbx1 in all myoblasts ( Fig.…”
Section: Discussionmentioning
confidence: 99%